Individual and Synergistic Anti-Coronavirus Activities of SOCS1/3 Antagonist and Interferon α1 Peptides - Ahmed, Chulbul M.; Grams, Tristan R.; Bloom, David C.; Johnson, Howard M.; Lewin, Alfred S. (Frontiers in Immunology, 2022)
Suppressors of Cytokine Signaling (SOCS) are intracellular proteins that negatively regulate the induction of cytokines. Amongst these, SOCS1 and SOCS3 are particularly involved in inhibition of various interferons. Several viruses have hijacked this regulatory pathway: by inducing SOCS1and 3 early in infection, they suppress the host immune response. Within the cell, SOCS1/3 binds and inhibits tyrosine kinases, such as JAK2 and TYK2. We have developed a cell penetrating peptide from the activation loop of the tyrosine kinase, JAK2 (residues 1001-1013), denoted as pJAK2 that acts as a decoy and suppresses SOCS1 and 3 activity. This peptide thereby protects against several viruses in cell culture and mouse models. Herein, we show that treatment with pJAK2 inhibited the replication and release of the beta coronavirus HuCoV-OC43 and reduced production of the viral RNA, as measured by RT-qPCR, Western blot and by immunohistochemistry. We confirmed induction of SOCS1 and 3 in rhabdomyosarcoma (RD) cells, and this induction was suppressed by pJAK2 peptide. A peptide derived from the C-terminus of IFN (IFN-C) also inhibited replication of OC43. Furthermore, IFN-C plus pJAK2 provided more potent inhibition than either peptide alone. To extend this study to a pandemic beta-coronavirus, we determined that treatment of cells with pJAK2 inhibited replication and release of SARS-CoV-2 in Calu-3 cells. We propose that these peptides offer a new approach to therapy against the rapidly evolving strains of beta-coronaviruses.